Can Dietary Fiber Intake Be Increased through Nutritional Education and through Subsidies on Selected Food Products?. (December 2019) - Senia, Mark Christopher; Dharmasena, Senarath; Capps, Oral
Abstract : Consumers in the United States fall short of meeting the recommended guideline for dietary fiber intake. Using a quarterly panel of households from Nielsen for the years 2004 through 2014, we employ a Heckman two-step approach to estimate nine panel regressions concerning per person fiber intakes derived from various food categories to uncover the importance of prices as well as socioeconomic and demographic factors. Prices play a prominent role in the per person intake of dietary fiber derived from the respective food products considered. Households below poverty thresholds had lower intakes of fiber relative to households above poverty thresholds. Ethnicity, race, age of the household head, region, and the presence of children also had significant effects on dietary fiber derived from the respective food categories. A proposed 20 percent subsidy applied to fruits and vegetables would increase per person intake of fiber by 9.4 percent. Therefore, if one were to consider meeting the dietary fiber requirement only through the provision of a subsidy, a large subsidy applied to fruits and vegetables would be required. Therefore, given the complex nature of the various factors affecting the intake of dietary fiber, the feasibility of using subsidies alone to increase the intake of dietary fiber is called into question.